Political parties and disinformation. Can governments defend the truth? Considerations about the "Permanent Commission against Disinformation" of the Spanish Government and Other Alternatives - Hernando-Masdeu, Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Following the 2016 US elections and the scandal around Facebook and Cambridge Analytica in 2018, the EU and several of its members promoted initiatives to fight disinformation. This paper focuses on one instrument, the "Permanent Commission against disinformation", created by the Government of Spain in 2020. It analyzes its background, parliamentary debates and early work, as well as similar instruments in Europe and USA. And it is hypothesized that this type of tool may not be an adequate solution to the problem.